Studying psychotherapy change in narrative terms: the innovative moments method - Batista, João (2020)
This paper aims to describe the Innovative Moments (IM) Coding System (IMCS), an idiographic and transtheoretical methodology that allows the identification of IMs-markers of changes in the client's initial maladaptive framework of meaning-throughout psychotherapy. The present study introduces the theoretical background underlying this methodology, along with the main empirical findings resulting from former studies that have applied this tool to clinical data. The IMCS application is also detailed: the coding phases, the training steps and inter-rater agreement measures. In order to illustrate the application of IM coding, a case study is presented. Although a partial coding was used, the results are in line with previous research. Discussion is centred on the usefulness of the IMCS for the advance of process research in psychotherapy, and the potential use of this methodology in group format.